Sistem Pakar Diagnosa Penyakit Katarak dengan Metode Certainty Factor - Mortara, Alda Amalia; Anita Desiani (JURNAL AMPLIFIER : JURNAL ILMIAH BIDANG TEKNIK ELEKTRO DAN KOMPUTER, 2023)
The eye is one of the most vital parts of the human body, which of course must be maintained. Unhealthy eyes will have a bad impact on the sufferer because it can interfere with the sufferer's activity process. One of the simplest and most common eye diseases suffered by humans is cataracts. Symptoms of cataracts occur painlessly so that many sufferers do not realize that they have cataracts. In Indonesia, the main cause of visual impairment and blindness is cataracts. Cases of blindness caused by cataracts occur due to a condition where the lens of the eye becomes cloudy and cataracts do not only occur at an early age but at all ages even though cataracts are a type of blindness that can be avoided and can be cured through treatment. Therefore an expert system is needed to help diagnose cataracts so that prevention can be done as much as possible. One method that can be used by expert systems is the assurance factor method. The advantage of the assurance factor method is that it can provide settlement solutions with the value of disease symptoms given by experts. With the superiority of the assurance factor method, this study will discuss the application of the assurance factor in the diagnosis of cataracts. To diagnose cataracts, there are 18 symptoms with 3 types of disease, namely congenital, juvenile, and traumatic cataracts. This study used 5 data tests based on the symptoms felt by people with cataracts to produce accurate predictions for each type of cataract where 86.0762% congenital cataracts in the first test data, 94.0595% juvenile cataracts in the second test data, 92.5128% traumatic cataracts in the third test data, 92.2440 % juvenile cataracts in the fourth test data, and 90.2080% juvenile cataracts in the fifth test data.